Implementasi Nilai - Nilai Persatuan Dan Gotong Royong Pada Petani (Studi Kasus pada Kelompok Tani Subur Makmur di Desa Lempong Kecamatan Jenawi Kabupaten Karanganyar Tahun 2016) - Muslimin, Derajat; , Dra. Hj. Sri Arfiah, S.H., M.Pd (2017)
This study aimed to describe the values of unity and cooperation. Data was collected by interview, observation and documentation. This research strategy is a single case study. A single case study was only conducted research on a target, the location and subject. It can be concluded that the form of the values of unity and mutual assistance to farmers in the Lempong Jenawi District of Karanganyar realized with; 1) holds regular meetings once every month, 2) in regular meetings always included a mandatory fee for all members of the nominal value of Rp. 10.000, - and gathering members, 3) members of farmer groups fertile prosperous until recently had the pleasure to be members because getting real assistance such as seeds of crops and livestock, 4) One result of the meeting that is often done is the implementation of mutual cooperation for the entire group. Barriers that have often arises is for group members who did not attend two consecutive usually go into town to look for additional work and their laziness are found but only one or two members. Solutions to overcome obstacles when there are members who have to work outside the village, the meeting represented by one member of the family.